2019
DOI: 10.1186/s40942-019-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

Anterior chamber paracentesis during intravitreal injections in observational trials: effectiveness and safety and effects

Abstract: A paracentesis prior to an intravitreal injection is a very safe procedure and can prevent IOP-spikes after injections. As these spikes pose the risk of inducing glaucomatous changes particularly in patients with frequent injections and/or with a risk profile, a regular paracentesis prior to an injection may be considered and discussed with the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…The mean IOP normalized at 15 min for the pretreatment group, whereas this was only the case after 30 min for the control group 112 . Additionally, several studies have shown that prophylactic anterior chamber paracentesis is a safe and effective option for preventing IOP spikes after an intravitreal injection 87,113,114 . Most notably, Enders et al found a significant RNFL-loss in patients who had not undergone anterior chamber paracentesis prior to their intravitreal injections, but could not find a significant reduction in RNFL-thickness in those who did 115 .…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…The mean IOP normalized at 15 min for the pretreatment group, whereas this was only the case after 30 min for the control group 112 . Additionally, several studies have shown that prophylactic anterior chamber paracentesis is a safe and effective option for preventing IOP spikes after an intravitreal injection 87,113,114 . Most notably, Enders et al found a significant RNFL-loss in patients who had not undergone anterior chamber paracentesis prior to their intravitreal injections, but could not find a significant reduction in RNFL-thickness in those who did 115 .…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Ocular fluids comprising AH and vitreous humor have been reported to reflect intraocular immune environment in AMD ( 17 , 18 , 31 ), proliferative diabetic retinopathy ( 32 ), and uveitis ( 33 , 34 ). Since sampling of AH is easier and safer compared to vitreous fluid ( 17 , 18 ), AH has been recognized as an ideal biological specimen to examine the pathology of ocular diseases ( 35 ). Our group has reported the participation of inflammatory cytokines including IP-10, MCP-1, and MIP-1β in the pathophysiology of nAMD ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…ППК регулярно применяют в качестве профилактики повышения ВГД после интравитреальных инъекции анти-VEGF препаратов, глюкокортикостероидов и др. [6,20].…”
Section: Discussionunclassified